Internal design for housing using AR - Khong, Lin Yan (2021)
This project is about using AR technology to perform ease for interior designing a house. Augmented Reality is a technology where it helps users to see virtual things in a more realistic point of view. People nowadays are using measuring tape to tape around their house in order to image out their house so that they could choose the right furniture needed. The AR technology that were used here are measuring the room outline and showing the furniture. It allows furniture to be inserted with a correct measurement as the real world and helps users to measure their room then outline them. In this project, the room is outlined according to the corners that were manually declared by users and the furniture will change the view size when moving around the room. The best thing of this project is where the “dream house” could be a reality after designing it as it will include a tracking for those who would like to see how their room could go from not expected to the way they designed.